From rhetoric towards a model of practical knowledge management systems - Xu, J.; Quaddus, Mohammed (Emerald Group Publishing, 2005)
Purpose - this paper aims to investigate the factors influencing the adoption and diffusion of knowledge management systems (KMSs) in Australia. Design/methodology/approach - A qualitative field study was undertaken, in which six Australian organizations of various sizes, all in various stages of KMS adoption and diffusion, were studied via face-to-face interviews with key personnel in the organizations. Findings - A comprehensive combined model of adoption and diffusion of KMS was developed and is presented in detail. Practical limitations/implications - This paper explains how the combined model can be used for practical applications in companies that are embarking on KMS adoption and diffusion. Originality/value - This study contributes to the KMS literature by taking a qualitative research approach to develop a comprehensive model.